A ‘patient’ aesthetic: Exploring the visual language of Italian urban landscape photographer Gabriele Basilico - Tommasini, Alexandra (Journal of European studies, 2017)
This article stakes a claim on the word ‘patient’, both its nominal and adjectival format, as a discursive tool to explore Italian photographer Gabriele Basilico’s visual language. The ‘patient’ metaphor is also employed to investigate the critical questions regarding the status of the documentary value of Basilico’s work. The discussion focuses on four exemplary photographs that span Basilico’s career and depict European and international cities in order to understand the slow unfolding of his aesthetic throughout his over 30-year career. It debates the extent to which Basilico’s visual language could be interpreted as avoiding engagement with the subject pictured, and in so doing offers critical interpretations of Basilico’s persistent gaze on the built environment.